2020
DOI: 10.7150/thno.45989
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA CSMD1-1 promotes the progression of Hepatocellular Carcinoma by activating MYC signaling

Abstract: Emerging evidence suggests that long non-coding RNAs (lncRNA) play critical roles in the development and progression of diverse cancers including hepatocellular carcinoma (HCC), but the underlying molecular mechanisms of lncRNAs that are involved in hepatocarcinogenesis have not been fully explored. Methods: In this study, we profiled lncRNA expression in 127 pairs of HCC and nontumor liver tissues (a Discovery Cohort) using a custom microarray. The expression and clinical significance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…Long non-coding RNAs (lncRNAs) refer to non-coding RNAs consisting of >200 nucleotides. Increasing studies have reported lncRNAs play vital roles in cancer cell proliferation, metastasis and chemoresistance 14 - 17 . Moreover, the lncRNAs tend to exhibit higher tissue-specific expressions than protein coding genes 18 - 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) refer to non-coding RNAs consisting of >200 nucleotides. Increasing studies have reported lncRNAs play vital roles in cancer cell proliferation, metastasis and chemoresistance 14 - 17 . Moreover, the lncRNAs tend to exhibit higher tissue-specific expressions than protein coding genes 18 - 20 .…”
Section: Introductionmentioning
confidence: 99%
“…In liver cancer, two lncRNAs GHET1 and CSMD1-1 stabilize activating transcription factor 1 (ATF1) mRNA expression or c-Myc protein respectively, by binding to its protein to regulate cancer cell migration and invasion [ 50 , 51 ]. Involvement of the EZH2 protein in the migration and invasion processes of cancer has also been highlighted with various lncRNAs.…”
Section: Lncrna–protein Interaction In Cancer Developmentmentioning
confidence: 99%
“…At the same time, lncCSMD1-1 interacted with MYC protein to block its ubiquitin-proteasome degradation pathway, thereby activating its downstream target gene. 17 Research by Xu et al found that the expression of lncRNA H19 was negatively correlated with sorafenib sensitivity in HCC cells. Inhibition of lncRNA H19 could increase the sensitivity of sorafenib by inhibiting the epithelial-mesenchymal transition (EMT) of HCC cells.…”
Section: Introductionmentioning
confidence: 99%